The Influence of Cyclic Sintering on the Structure and Mechanical Properties of Tungsten Heavy Alloy - Skoczylas P.; Kaczorowski M. (Archives of Foundry Engineering, 2016)
The results of structure and mechanical properties investigations of tungsten heavy alloy (THA) after cyclic sintering are presented. The material for study was prepared using liquid phase sintering of mixed and compacted powders in hydrogen atmosphere. The specimens in shape of rods were subjected to different number of sintering cycles according to the heating schemes given in the main part of the paper From the specimens the samples for mechanical testing and structure investigations were prepared. It follows from the results of the mechanical studies, that increasing of sintering cycles lead to decrease of tensile strength and elongation of THA with either small or no influence on yield strength. In opposite to that, the microstructure observations showed that the size of tungsten grain increases with number of sintering cycles. Moreover, scanning electron microscope (SEM) observations revealed distinctly more trans-granular cleavage mode of fracture in specimens subjected to large number of sintering cycles compared with that after one or two cycles only.